2019
DOI: 10.21276/aan.2019.4.2.42
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Comparison between Isobaric Bupivacaine Fentanyl and Isobaric Ropivacaine Fentanyl for Lower Abdomoinaland Lower Limb Surgery

Abstract: Background: Spinal anesthesia is the most commonly used method of anaesthesia and analgesia in lower limb surgeries. Spinal anaesthesia causes more sympatholysis and haemodynamic disturbances than general anesthesia. A low dose of local anaesthetic is preferred which may occasionally cause failure of spinal anaesthesia. Therefore, different adjuvants are added to local anesthetic to achieve desired level anesthesia. Aim: The aim of this study was to compare intraoperative haemodynamic changes associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
5
8
0
Order By: Relevance
“…In the present study, the mean duration of sensory blockade was longer in Group I (241.57 ± 1.87 min) when compared with Group II (196.28 ± 1.57 min) and was statistically significant (P value < 0.001). Our results are in accordance with the study conducted by Varun S et al [6] Jagtap et al [15] compared 15 mg of 0.5% ropivacaine with 25 µg fentanyl and 15 mg of 0.5% bupivacaine with 25 µg fentanyl, and found out that the time to sensory regression to L1 dermatome was faster in the ropivacaine group compared with the bupivacaine group (P -0.36) which is similar to our results. Mantouvalou et al [16] in their study found out that the duration of sensory block was 230 minutes, 240 minutes and 200 minutes respectively, while comparing 15 mg of isobaric levobupivacaine with 15 mg of isobaric bupivacaine and 15 mg isobaric ropivacaine.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, the mean duration of sensory blockade was longer in Group I (241.57 ± 1.87 min) when compared with Group II (196.28 ± 1.57 min) and was statistically significant (P value < 0.001). Our results are in accordance with the study conducted by Varun S et al [6] Jagtap et al [15] compared 15 mg of 0.5% ropivacaine with 25 µg fentanyl and 15 mg of 0.5% bupivacaine with 25 µg fentanyl, and found out that the time to sensory regression to L1 dermatome was faster in the ropivacaine group compared with the bupivacaine group (P -0.36) which is similar to our results. Mantouvalou et al [16] in their study found out that the duration of sensory block was 230 minutes, 240 minutes and 200 minutes respectively, while comparing 15 mg of isobaric levobupivacaine with 15 mg of isobaric bupivacaine and 15 mg isobaric ropivacaine.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows a slight contrast with Breebaart et al [14] which can be explained due to the different dose of levobupivacaine used and also because no adjuvant was used in their study. In our study, highest sensory dermatome level reached was T6 level in both the groups, number of patients reaching the T6 sensory dermatome level block was comparable in both the groups which is similar to the study done by Srilakhshmi et al [2] and Varun et al [6] In our study, the onset of motor blockade was faster in Group I (3.53 ± 0.17min) than in Group II (4.48 ± 0.10 min).Our results are comparable to studies conducted by Indumathi et al, [12] Mehta et al [18] and Srilakshmi et al [2] Total duration of motor blockade was longer in Group I (187.48 ± 12.12 min) than in Group II (160.75 ± 1.89 min).Our study is in accordance with the study of Kolkta et al [19] in which they compared the equipotent doses of isobaric ropivacaine and isobaric bupivacaine (19.5 mg and 13 mg respectively) with fentanyl 20 μg,, however the individual readings of motor block of ropivacaine group shows slight difference which may be due to the different dose of ropivacaine used. Our results are coinciding with the study conducted by Layek et al [20] in which the duration of motor block was significantly longer in group Bupivacaine when compared to group Ropivacaine in elective infraumbilical orthopedic surgery.(P<0.001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations